1991
DOI: 10.1002/mrd.1080300109
|View full text |Cite
|
Sign up to set email alerts
|

In vivo secretion and association of clusterin (SGP‐2) in luminal fluid with spermatozoa in the rat testis and epididymis

Abstract: Clusterin (sulfated glycoprotein-2) is a heterodimeric glycoprotein synthesized and secreted by rat Sertoli cells. An antigenically similar form is synthesized and secreted by the epididymis. The goal of this study was to define the epididymal regions in which clusterin is present and the regions in which clusterin is secreted and interacts with developing spermatozoa. Seminiferous tubule (STF), caput, corpus, and cauda fluids were collected by micropuncture and/or microperfusion and two-dimensional Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
23
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 32 publications
7
23
0
Order By: Relevance
“…Of these 28 proteins, 8 have been reported to have regionalized behavior within the epididymis, such as Gln synthetase 20 and clusterin. 21,22 Our results are highly accordant with the reports describing those proteins previously known to be regionalized (Table 1). In addition, our results are the first to reveal the regional distribution of four other previously identified epididymal proteins (Table 1).…”
Section: Resultssupporting
confidence: 91%
“…Of these 28 proteins, 8 have been reported to have regionalized behavior within the epididymis, such as Gln synthetase 20 and clusterin. 21,22 Our results are highly accordant with the reports describing those proteins previously known to be regionalized (Table 1). In addition, our results are the first to reveal the regional distribution of four other previously identified epididymal proteins (Table 1).…”
Section: Resultssupporting
confidence: 91%
“…In neuronal cells, early studies have shown that clusterin is accumulated in the apoptotic dying neurons in CA1 hippocampal pyramidal cells, and clusterin gene expression is strongly correlated with apoptosis (Rozovsky et al, 1994). Other studies have shown that an exogenously infected SGP-2 gene, does not induce apoptosis and that ApoJ expression is strongly associated with neuronal apoptosis in the olfactory mucosa (D'Mello et al, 1993;Michel et al, 1997). On the other hand, in the several photoreceptor neurons, clusterin is not causally involved in apoptosis, but may have cytoprotective functions (Jomary et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…In neuronal cells, early studies have shown that clusterin is accumulated in apoptotic dying neurons in the CA1 hippocampal pyramidal cells, and clusterin gene expression is strongly related to apoptosis (Rozovsky et al, 1994). On the other hand, other studies have reported that an exogenously infected SGP-2 gene does not induce apoptosis (D'Mello et al, 1993). The biological function of clusterin associated with apoptosis in neurocytes is unclear.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Sertoli cells and epididymal epithelial principal cells have been shown to synthesize and secrete a number of glycoproteins that have been suggested to play important roles in the regulation of spermatogenesis and sperm maturation [3]. One of the major proteins secreted by both Sertoli cells and epididymal epithelial cells is sulfated glycoprotein-2 (SGP-2) [4]. SGP-2 is a heavily glycosylated protein composed of two monomers that arise from a proteolytically-cleaved, single chain polypeptide precursor [5].…”
mentioning
confidence: 99%